SOCIO-ECONOMIC AND DEMOGRAPHIC PROCESSES AFFECTING THE FAMILY INSTITUTE - Inoyatova Saodatkhan Jahangir's daughter (Web of Journals Publishing, 2023)
This article is based on the need to build it on healthy foundations, to form strong families and to protect the family model specific to the Uzbek family in the form of national moral values of the family. The family has been revealed to be the object of study as the world's best social model for its longevity and stability.
Keywords: Family, lifestyle, ethics, husband and wife, family model, civil society, social factors.